High-rate silicon-carbon negative electrode material and preparation method and application thereof
By using porous carbon cores, nanosilicon particles and organic cracked carbon coating in lithium-ion batteries, high-ratio silicon carbon anode material, combined with conductive carbon additives, nitrogen elements and phosphorus elements, the charging volume expansion of silicon anode material is solved and Impedance issues improve the rate performance and energy density of the battery.
Patent Information
- Application Number
- CN202411640788.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Silicon negative electrode materials have a large charging volume expansion and impedance in lithium-ion batteries, which limits the improvement of their rate performance and energy density. It is difficult for the existing technology to effectively solve these problems.
Using high-ratio silicon carbon anode material with porous carbon cores, nanosilicon particles and organic cracked carbon coating, the conductive pathways are formed and surface properties are adjusted by introducing conductive carbon additives, nitrogen and phosphorus elements into the porous carbon cores, and the charging is reduced. Discharge impedance and expansion.
It significantly reduces the charging volume expansion and charge and discharge impedance, improves the rate performance and energy density of lithium-ion secondary batteries, and is suitable for industrial production.
Smart Images

Figure CN119170785A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and in particular to a high-rate silicon-carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] With the development of consumer electronics, new energy vehicles and electric aircraft, the market demand for high energy density and fast charging electrode materials is becoming more and more urgent. The theoretical gram capacity of graphite negative electrode material is only 372mA·h / g, while silicon material has a theoretical gram capacity of 4200mA·h / g. When alloyed at room temperature to form Li 15 Si4, the gram capacity can reach 3579mA·h / g, so the use of silicon material in the negative electrode of the battery can greatly improve the energy density of the battery.
[0003] Although silicon material has high gram capacity, it also has huge volume expansion when charged. Excessive volume expansion can easily lead to particle rupture, causing the negative electrode capacity to decay rapidly and resulting in insufficient battery cycle performance. At the same time, silicon, as a semiconductor material, has a large impedance, and high-rate charge and discharge processes can easily produce large polarization, which limits its application in terminal products.
[0004] At present, the application of silicon negative electrode materials mostly adds special conductive agents and binders during the slurry process to achieve the effect of reducing impedance and limiting expansion, but the impedance and expansion inside the silicon material have not been significantly improved.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] One of the purposes of the present invention is to provide a high-rate silicon-carbon negative electrode material with small charge and discharge impedance, small charging volume expansion, high first reversible capacity and high first efficiency, which is beneficial to improving the rate performance and energy density of lithium-ion secondary batteries.
[0007] The second object of the present invention is to provide a method for preparing a high-rate silicon-carbon negative electrode material, which has a simple process and is suitable for industrial production. It can reduce the charge and discharge impedance of the negative electrode material and also enable the negative electrode material to have a lower charging volume expansion.
[0008] The third object of the present invention is to provide an application of a high-rate silicon-carbon negative electrode material, which can effectively improve the rate performance and energy density of lithium-ion secondary batteries and achieve outstanding application effects.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: In the first aspect, a high-rate silicon-carbon negative electrode material comprises a porous carbon core, nano-silicon particles and an organic cracked carbon coating layer; The porous carbon core contains a conductive carbon additive, nitrogen and phosphorus; The nano silicon particles are dispersed in the internal pores and the surface pores of the porous carbon core; The conductive carbon additive is interspersed in the gaps between the nano-silicon particles and the porous carbon core; The nitrogen element is present in the porous carbon core in the form of pyridinic nitrogen, pyrrolic nitrogen and / or graphitic nitrogen; The phosphorus element is distributed in the porous carbon core at the molecular and / or atomic level; The organic cracked carbon coating layer is distributed in the pores and outer surface of the porous carbon core.
[0010] Furthermore, the conductive carbon additive accounts for 0.01wt% to 1wt% in the silicon-carbon negative electrode material; Preferably, the total proportion of the nitrogen element and the phosphorus element in the silicon-carbon negative electrode material is 0.01wt%~1wt%; Preferably, the average particle size D50 of the silicon-carbon negative electrode material is 0.5 μm to 5 μm.
[0011] Further, the conductive carbon additive includes at least one of zero-dimensional conductive carbon, one-dimensional conductive carbon and two-dimensional conductive carbon; Preferably, the size of the zero-dimensional conductive carbon is 0.1 nm to 100 nm; Preferably, the one-dimensional conductive carbon has a diameter of 0.1 nm to 50 nm and a length of 100 nm to 2000 nm; Preferably, the two-dimensional conductive carbon has a thickness of 0.1 nm to 10 nm and a diameter of 100 nm to 500 nm.
[0012] Furthermore, the pore volume of the silicon-carbon negative electrode material is less than 0.01 cm³ / g; Preferably, the most probable pore size of the silicon-carbon negative electrode material is below 3 nm; Preferably, the specific surface area of the silicon-carbon negative electrode material does not exceed 5 m² / g.
[0013] Furthermore, the grain size of the nano-silicon is below 2 nm; Preferably, the nano-silicon accounts for 10wt% to 90wt% in the silicon-carbon negative electrode material; Preferably, the organic cracked carbon coating layer accounts for 0.1wt% to 10wt% in the silicon-carbon negative electrode material.
[0014] In a second aspect, a method for preparing the silicon-carbon negative electrode material described in any one of the above items comprises the following steps: The hard carbon precursor is pyrolyzed and carbonized to obtain porous carbon, the porous carbon is used to adsorb silane compounds, and then the silane compounds are pyrolyzed in the porous carbon to deposit nano-silicon particles, and then the pores and outer surface of the porous carbon core are coated with an organic cracked carbon layer to obtain the silicon-carbon negative electrode material; The hard carbon precursor is doped with conductive carbon additives, nitrogen and phosphorus.
[0015] Furthermore, the method for preparing the hard carbon precursor comprises the following steps: The soluble biomass raw material is mixed with a conductive carbon additive, a nitrogen compound, a phosphorus compound and water to react, so that the biomass raw material is dehydrated and polymerized to obtain the hard carbon precursor; Wherein, the biomass raw material includes at least one of monosaccharides, disaccharides and polysaccharides; The temperature of the mixed reaction is 150°C to 375°C.
[0016] Furthermore, the temperature of the pyrolysis carbonization is 400° C. to 1000° C., and the time of the pyrolysis carbonization is 1 h to 12 h.
[0017] Furthermore, the pyrolysis temperature of the silane compound is 400° C. to 700° C., and the pyrolysis time is 1 h to 12 h.
[0018] A third aspect is an application of the silicon-carbon negative electrode material described in any one of the above items in a lithium-ion secondary battery.
[0019] Compared with the prior art, the present invention has at least the following beneficial effects: The high-rate silicon-carbon negative electrode material provided by the present invention contains a conductive carbon additive, a nitrogen element and a phosphorus element. The conductive carbon additive, the nitrogen element and the phosphorus element and their specific contents can effectively reduce the charge and discharge impedance of the negative electrode material. The silicon-carbon negative electrode material has a smaller average particle size (the average particle size D50 is 0.5μm~5μm), and with a smaller silicon grain size (for example, the grain size is below 2nm), it can significantly reduce the charging volume expansion, and also has a higher first reversible capacity and a higher first efficiency, so it is beneficial to improve the rate performance and energy density of the lithium-ion secondary battery.
[0020] The preparation method of the high-rate silicon-carbon negative electrode material provided by the present invention not only has a simple process, a high success rate, and is suitable for industrial production, but also can effectively reduce the charge and discharge impedance of the negative electrode material, and can also make the negative electrode material have a lower charging volume expansion.
[0021] The application of the high-rate silicon-carbon negative electrode material provided by the present invention can effectively improve the rate performance and energy density of lithium-ion secondary batteries, and achieves outstanding application effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 A 2000-fold scanning electron microscope image of the silicon-carbon negative electrode material provided in Example 1 of the present invention; Figure 2 This is a 30,000-fold scanning electron microscope image of the silicon-carbon negative electrode material provided in Example 1 of the present invention; Figure 3 The first charge and discharge curve of the lithium button cell of the silicon-carbon negative electrode material obtained in Experimental Example 2 of the present invention; Figure 4 This is the first charge and discharge dQ / dV curve of the lithium button cell with the silicon-carbon negative electrode material obtained in Experimental Example 2 of the present invention. DETAILED DESCRIPTION
[0024] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] According to a first aspect of the present invention, there is provided a high-rate silicon-carbon negative electrode material, comprising a porous carbon core, nano-silicon particles and an organic cracked carbon coating layer; In the present invention, the porous carbon core contains a rich pore structure; Specifically, the porous carbon core contains a conductive carbon additive, nitrogen and phosphorus; Nano-silicon particles are dispersed in the internal pores and surface pores of the porous carbon core; The conductive carbon additive is interspersed in the gaps between the nano-silicon particles and the porous carbon core; The nitrogen element exists in the porous carbon core in the form of pyridinic nitrogen, pyrrolic nitrogen and / or graphitic nitrogen; The phosphorus element is distributed in the porous carbon core at the molecular and / or atomic level; The organic pyrolysis carbon coating layer is distributed in the pores and outer surface of the porous carbon core.
[0026] In the present invention, the conductive carbon additive distributed inside the silicon-carbon negative electrode material can increase the conductive path of nano-silicon and porous carbon, the introduction of nitrogen element can improve the sp2 hybridization of the carbon material, thereby improving the conductivity of the material, and phosphorus doping can adjust the surface properties of the carbon material to a greater extent by converting the sp2 hybridized carbon into an sp3 state and allowing phosphorus to form a pyramid-shaped bonding structure with three carbon atoms, thereby introducing more defect sites and improving the battery rate performance.
[0027] In a preferred embodiment, the proportion of the conductive carbon additive in the silicon-carbon negative electrode material can be 0.01wt%~1wt%, and its typical but non-limiting proportion is, for example, 0.01wt%, 0.05wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, and 1wt%. The appropriate proportion of the conductive carbon additive is more conducive to further reducing the charge and discharge impedance and improving the energy density balance; if the proportion of the conductive carbon additive is too high, the proportion of the active material in the battery will be too low, resulting in too low energy density of the entire battery; if the proportion of the conductive carbon additive is too low, the conductivity of the material cannot be effectively improved.
[0028] In a preferred embodiment, the total proportion of nitrogen and phosphorus in the silicon-carbon negative electrode material can be 0.01wt%~1wt%, and its typical but non-limiting total proportion is, for example, 0.01wt%, 0.05wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, and 1wt%. The appropriate total proportion of nitrogen and phosphorus is more conducive to further reducing the charge and discharge impedance and balancing the battery energy density and the initial efficiency; if the total proportion of nitrogen and phosphorus is too high, it will lead to too many defects and consume too many active lithium ions, thereby reducing the initial efficiency and energy density of the battery; if the total proportion of nitrogen and phosphorus is too low, it will cause insufficient conductivity and defects, and the impedance cannot be effectively reduced and the rate performance cannot be improved.
[0029] In a preferred embodiment, the average particle size D50 of the silicon-carbon negative electrode material can be 0.5μm~5μm, and its typical but non-limiting average particle size D50 is, for example, 0.5μm, 1μm, 2μm, 3μm, 4μm, and 5μm. Combined with a smaller silicon grain size (for example, a grain size below 2nm), the charging volume expansion can be significantly reduced.
[0030] In summary, the high-rate silicon-carbon negative electrode material provided by the present invention, with the coordinated cooperation of various parameters, not only has a small charge and discharge impedance and a small charging volume expansion, but also has a high first reversible capacity and a high first efficiency, which is beneficial to improving the rate performance and energy density of lithium-ion secondary batteries.
[0031] In a preferred embodiment, the conductive carbon additive includes but is not limited to at least one of zero-dimensional conductive carbon, one-dimensional conductive carbon and two-dimensional conductive carbon.
[0032] In the present invention, the size of the zero-dimensional conductive carbon can be 0.1nm~100nm, for example, it can be 0.1nm, 0.5nm, 1nm, 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, but not limited to this; the diameter of the one-dimensional conductive carbon can be 0.1nm~50nm, for example, it can be 0.1nm, 0.5nm, 1nm, 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, but not limited to this; the length of the one-dimensional conductive carbon can be 100nm~2000nm, for example, it can be 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1500nm, 2000nm, but not limited to this; the thickness of the two-dimensional conductive carbon can be 0.1nm~10nm, for example, it can be 0.1nm, 0.5nm, 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, but not limited to this; the diameter of the two-dimensional conductive carbon can be 100nm~500nm, for example, it can be 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, but not limited to this.
[0033] In a preferred embodiment, the pore volume of the silicon-carbon negative electrode material may be less than 0.01 cm³ / g, the most probable pore size of the silicon-carbon negative electrode material may be less than 3 nm, and the specific surface area of the silicon-carbon negative electrode material may not exceed 5 m² / g.
[0034] In a preferred embodiment, the grain size of nano-silicon may be less than 2 nm.
[0035] Nano-silicon particles are distributed inside the silicon-carbon material. The smaller average particle size of the silicon-carbon negative electrode material combined with the smaller silicon grain size can further reduce the charging volume expansion of the material.
[0036] In the present invention, the proportion of nano-silicon in the silicon-carbon negative electrode material can be 10wt%~90wt%, and its typical but non-limiting proportion is, for example, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, and 90wt%.
[0037] In a preferred embodiment, the proportion of the organic cracked carbon coating layer in the silicon-carbon negative electrode material can be 0.1wt%~10wt%, and its typical but non-limiting proportions are, for example, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, and 10wt%.
[0038] According to a second aspect of the present invention, there is provided a method for preparing the silicon-carbon negative electrode material as described in any one of the above, comprising the following steps: The hard carbon precursor is pyrolyzed and carbonized to obtain porous carbon, and the porous carbon is used to adsorb silane compounds, and then the silane compounds are pyrolyzed in the porous carbon to deposit nano-silicon particles, and then the pores and the outer surface of the porous carbon core are coated with an organic cracked carbon layer to obtain a silicon-carbon negative electrode material; The hard carbon precursor is doped with conductive carbon additives, nitrogen and phosphorus.
[0039] The preparation method of the high-rate silicon-carbon negative electrode material provided by the present invention not only has a simple process, a high success rate, and is suitable for industrial production, but also can effectively reduce the charge and discharge impedance of the negative electrode material, and can also make the negative electrode material have a lower charging volume expansion.
[0040] In a preferred embodiment, the method for preparing the hard carbon precursor comprises the following steps: The soluble biomass raw material is mixed with a conductive carbon additive, a nitrogen compound, a phosphorus compound and water to react, so that the biomass raw material is dehydrated and polymerized to obtain a hard carbon precursor; Wherein, the biomass raw materials include but are not limited to at least one of monosaccharides, disaccharides and polysaccharides; The temperature of the mixed reaction can be 150°C to 375°C, for example, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 325°C, 350°C, 375°C, but is not limited thereto.
[0041] The present invention prepares a hard carbon precursor containing a conductive carbon additive, nitrogen and phosphorus elements, wherein the conductive carbon additive, nitrogen and phosphorus elements are doped inside the hard carbon precursor during its generation process, and then the hard carbon precursor is pyrolyzed and carbonized to obtain porous carbon, and then the porous carbon is adsorbed with silane compounds for pyrolysis to obtain a silicon-carbon negative electrode material.
[0042] In a preferred embodiment, the temperature of pyrolysis carbonization can be 400°C~1000°C, and typical but non-limiting temperatures include 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, and 1000°C. The time of pyrolysis carbonization can be 1h~12h, and typical but non-limiting times include 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, and 12h. The above-mentioned pyrolysis carbonization temperature and time are more conducive to fully carbonizing the hard carbon precursor, and are more conducive to further ensuring the formation effect of porous carbon.
[0043] In a preferred embodiment, the pyrolysis temperature of the silane compound can be 400°C~700°C, and typical but non-limiting temperatures are, for example, 400°C, 500°C, 600°C, and 700°C. The pyrolysis time can be 1h~12h, and typical but non-limiting times are, for example, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, and 12h. The pyrolysis temperature and time are more conducive to ensuring sufficient pyrolysis of the silane compound, and are more conducive to further improving the formation effect of the silicon-carbon negative electrode material.
[0044] According to a third aspect of the present invention, there is provided a use of the silicon-carbon negative electrode material described in any one of the above items in a lithium-ion secondary battery.
[0045] The application of the high-rate silicon-carbon negative electrode material provided by the present invention can effectively improve the rate performance and energy density of lithium-ion secondary batteries, and achieves outstanding application effects.
[0046] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0047] Example 1 A method for preparing a high-rate silicon-carbon negative electrode material comprises the following steps: S1: 10 kg sucrose, 40 g conductive carbon black, 1 mol monoammonium phosphate and 100 kg pure water were mixed in a high-pressure reactor, the pressure in the reactor was controlled to be 2 MPa, and the reaction was carried out at a temperature of 200 ° C for 5 h to obtain a hard carbon precursor; S2: In an atmosphere of 80% nitrogen and 20% carbon dioxide, the hard carbon precursor of step S1 is pyrolyzed and carbonized at a temperature of 800°C for 4 hours, and then pulverized by air flow to obtain porous carbon; S3: The porous carbon in step S2 is pyrolyzed with monosilane and acetylene in a nitrogen atmosphere furnace at 550°C for 4 hours to obtain a silicon-carbon negative electrode material, whose physical and chemical index parameters are shown in Table 1.
[0048] The 2000-fold scanning electron microscope image of the silicon-carbon negative electrode material of this embodiment is shown in Figure 1 , 30000 times scanning electron microscope image see Figure 2 .
[0049] Example 2 The difference between this embodiment and embodiment 1 is that in step S1, this embodiment replaces sucrose with potato starch, and replaces 40g of conductive carbon black with 10g of graphene; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon negative electrode material, and its physical and chemical index parameters are shown in Table 1.
[0050] Example 3 The difference between this embodiment and embodiment 1 is that in step S1, this embodiment replaces 40g of conductive carbon black with 10g of carbon nanotubes; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon negative electrode material, and its physical and chemical index parameters are shown in Table 1.
[0051] Example 4 The difference between this embodiment and embodiment 1 is that in step S1, this embodiment replaces 1 mol of monoammonium phosphate with 0.5 mol of ammonium tripolyphosphate; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon negative electrode material, and its physical and chemical index parameters are shown in Table 1.
[0052] Example 5 The difference between this embodiment and embodiment 1 is that in step S3, the pyrolysis temperature of this embodiment is 600°C; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon negative electrode material, and its physical and chemical index parameters are shown in Table 1.
[0053] Comparative Example 1 The difference between this comparative example and Example 1 is that in step S1, conductive carbon black and monoammonium phosphate are not added in this comparative example; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon negative electrode material, and its physical and chemical index parameters are shown in Table 1.
[0054] Comparative Example 2 The difference between this comparative example and Example 1 is that in step S1, sucrose is replaced by cellulose in this comparative example, and conductive carbon black and monoammonium phosphate are not added; meanwhile, in step S2, conductive carbon black and monoammonium phosphate are added during pyrolysis and carbonization in this comparative example; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon negative electrode material, and its physical and chemical index parameters are shown in Table 1.
[0055] Comparative Example 3 The difference between this comparative example and Example 1 is that in step S3, the pyrolysis temperature of this comparative example is 850°C; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon negative electrode material, and its physical and chemical index parameters are shown in Table 1.
[0056] Comparative Example 4 The difference between this comparative example and Example 1 is that in step S1, this comparative example replaces 40 g of conductive carbon black and 1 mol of monoammonium phosphate with 200 g of conductive carbon black and 0.5 mol of ammonium tripolyphosphate; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon negative electrode material, and its physical and chemical index parameters are shown in Table 1.
[0057] Test Example 1 The physical and chemical index parameters of the silicon-carbon negative electrode materials obtained in Examples 1-5 and Comparative Examples 1-4 are shown in Table 1.
[0058] The particle size (μm) range of the material was tested using Dandong Better Laser Particle Sizer BT-9300ST; The specific surface area (m² / g) of the material was tested using JW-DX dynamic adsorption specific surface area meter. The resistance of the powder is accurately measured using GEST-126. The material was analyzed by XRD diffractometer (Panalytical X'PERT PRO MPD, Netherlands) to determine the grain size of the material; The pore size distribution of the material is tested using the American Quantachrome Autosorb IQ3; The contents of metal elements and non-metal elements were analyzed using the German SPECTRO ICP-OES plasma emission spectrometer GREEN.
[0059] Table 1
[0060] As can be seen from Table 1, in Examples 1-5 and Comparative Examples 1-4, the content, type and addition process of the conductive carbon additive have a great influence on the conductivity; in Example 1, there are more conductive carbon additives, but its conductivity is not as good as that of Examples 2 and 3. The reason is that the conductive carbon additives in Examples 2 and 3 are graphene and carbon nanotubes, respectively, both of which have excellent conductivity and can produce higher conductivity even if the addition amount is small; it can be seen from Examples 1 and 4 that when the addition amount of conductive carbon additives is the same, increasing the content of nitrogen (N) and phosphorus (P) elements can also improve the conductivity; the silicon content in Example 5 is higher, so the conductivity of Example 5 is lower than that of Example 1; in Comparative Example 1, no conductive carbon additives, nitrogen (N) and phosphorus (P) are added. and phosphorus (P) elements, resulting in the lowest conductivity; the conductivity of Comparative Example 2 is lower than that of Example 1, mainly because the conductive carbon additive and monoammonium phosphate were not added to the liquid phase system at the initial stage of the reaction, but were added in the pyrolysis and carbonization stage, which resulted in the conductive carbon additive, nitrogen (N) and phosphorus (P) elements being only dispersed on the surface of the material particles and unable to be evenly dispersed inside the particles, and therefore unable to significantly improve the overall conductivity of the particles; the conductivity of Comparative Example 3 is lower than that of Example 1, mainly because the temperature at which silane decomposes into nano-silicon is high, resulting in a high silicon content and poor silicon conductivity; more conductive carbon additives are added in Comparative Example 4, and the conductivity is high, but as can be seen from Table 2, too much conductive carbon additive will reduce the silicon content ratio, resulting in a decrease in the first reversible capacity and a decrease in energy density.
[0061] Test Example 2 The first reversible capacity and first efficiency of the silicon-carbon negative electrode materials obtained in Examples 1-5 and Comparative Examples 1-4 were tested as follows: Silicon-carbon negative electrode material, conductive carbon black and binder are mixed in pure water at a mass ratio of 94.5:1.5:4, homogenized, and the solid content is controlled to be 48wt%, coated on a copper foil current collector, vacuum-baked at 100°C for 8h, pressed and formed, and then punched to prepare a negative electrode sheet; The button half-cell was assembled in a glove box filled with argon. The counter electrode was a metal lithium sheet, the separator used was PE, and the electrolyte was 1 mol / L LiPF6 EC / DMC (Vol 1:1). The button cell was charged and discharged. The test process was 0.2C DC to 0V, 0.05C DC to 0V, 0V CV50μA, 0.01C DC to 0V, 0V CV 20μA, Rest 10min, 0.2C CC to 1.5V. The first reversible capacity and efficiency of the silicon-carbon negative electrode material were measured. The testing equipment for the button battery was the LAND battery testing system of Wuhan Landian Electronics Co., Ltd.
[0062] Expansion rate test of silicon-carbon negative electrode material S600: The silicon-carbon negative electrode material is measured for the first reversible capacity by the above-mentioned charge-withdrawal test method, and then a certain amount of the same graphite negative electrode is mixed according to the calculation to mix the silicon-carbon negative electrode material to 600±5mA·h / g, abbreviated as S600; S600 mixed material, conductive carbon black and binder (mass ratio 92:2:6) were homogenized in pure water to control the solid content to 48%, and then coated on a current collector with copper foil as the substrate, and then vacuum baked at 90°C for 8 hours, pressed by a roller press, and then sliced by a slicing device to prepare a negative electrode sheet; the thickness of the negative electrode sheet was measured with a micrometer, recorded as T1, and the thickness of the substrate was measured as T2, and the data were recorded; Assemble button half-cells in an argon-filled glove box, with the counter electrode being a metal lithium sheet, the separator being a PE material, and the electrolyte being 1 mol / L LiPF6 EC / DMC (Vol 1:1); perform charge and discharge tests on the button cell, with the test process being 0.1CDC to 0.005V, 0.05C DC to 0.005V, 0.02C DC to 0.005V, Rest 10min, 0.1C CC to1.5V, 0.1C DC to 0.005V, 0.05C DC to 0.005V, 0.02C DC to 0.005V; measure the first reversible capacity and efficiency of the negative electrode material; The battery was disassembled and the thickness of the negative electrode material obtained was detected and recorded as T3. The first full-charge expansion data of the negative electrode material was calculated according to the formula F=(T3-T1) / (T1-T2), where F is the first full-charge expansion rate.
[0063] The button cell testing equipment is the LAND battery testing system of Wuhan Landian Electronics Co., Ltd.; the slicing equipment is the MSK-T10 button half-cell slicing equipment of Kejing; the micrometer detection equipment is the Japanese Mitutoyo 293-100-10; and the rolling equipment is the MSK-HRP-05 button half-cell slicing equipment of Kejing.
[0064] Silicon-carbon anode material rate performance test: Silicon-carbon anode powder, Super p, and LA133 were mixed in pure water at a mass ratio of 85:10:5, and the solid content was controlled to be 42%-50%, and then homogenized; The silicon-carbon negative electrode slurry is coated on the current collector with copper foil as the substrate with a coating thickness of 50um-80um, and is placed in a vacuum baking oven at 80℃-100℃ for vacuum baking for 4h-8h. The pole piece is cold pressed with a commercial roller pressing equipment of Kejing, and the compaction density is 1.0g / cc-1.3g / cc. The pole piece is sliced into a circular silicon negative electrode piece with a diameter of 15mm-22mm using a commercial slicing equipment of Kejing; The silicon-carbon negative electrode sheet, PE separator and electrolyte (lithium salt 1mol / L LiPF6 solvent EC / DMC Vol 1:1) were assembled into a CR2430 button battery in a glove box, the button battery was left to stand at room temperature for 2h-6h, and charged and discharged on the blue power test system at 0.1C to 0.005V, 0.05C to 0.005V, 0.02C to 0.005V, 0.1C to 1.5V, 0.3C to 0.005V, 0.2C to 1.5V, 0.5C to 0.005V, 0.2C to 1.5V, and then the capacity at different discharge rates was counted, and the rate retention rate = discharge capacity at different rates / first discharge capacity.
[0065] The above test results are shown in Table 2, and the first charge and discharge curve of the lithium button battery of the silicon-carbon negative electrode material of Example 1 is shown in Figure 3 The first charge and discharge dQ / dV curve of the lithium button cell of the silicon-carbon negative electrode material of Example 1 is shown in Figure 4 .
[0066] Table 2
[0067] It can be seen from Table 1 and Table 2 that the silicon-carbon negative electrode materials of Examples 1-4 have a smaller particle size D50, a smaller silicon grain size and a suitable proportion of silicon content, so the S600 first expansion rate is low, and the conductive carbon additive, nitrogen (N) and phosphorus (P) elements in a suitable proportion can maintain a higher first reversible capacity and rate retention rate. In the lithium-ion battery test system, the first reversible capacity can reach more than 1900 mA·h / g; the silicon content in Example 5 is relatively high, so the S600 first expansion rate will be slightly larger; in Comparative Example 1, since no conductive carbon additive, nitrogen (N) and phosphorus (P) elements are added, the conductivity is relatively low, resulting in a lower first reversible capacity. The amount and rate retention rate are low; in Comparative Example 2, since the conductive carbon additive, nitrogen (N) and phosphorus (P) elements are only dispersed on the surface, the conductivity is not significantly improved, resulting in a low first reversible capacity and rate retention rate; in Comparative Example 3, due to the high decomposition temperature of monosilane, the high silicon content and the large silicon grains, the S600 first expansion rate is large, and the high silicon content also leads to low conductivity, so the first reversible capacity and rate retention rate are low; in Comparative Example 4, due to the high proportion of conductive carbon additives, the silicon content is reduced, so the first reversible capacity is reduced, and the material particle size D50 is 7.5μm, resulting in a large first expansion rate of S600.
[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high rate silicon-carbon negative electrode material, characterized in that: It includes a porous carbon core, nano silicon particles and an organic cracked carbon coating layer; The porous carbon core contains a conductive carbon additive, nitrogen and phosphorus; The nano silicon particles are dispersed in the internal pores and the surface pores of the porous carbon core; The conductive carbon additive is interspersed in the gaps between the nano-silicon particles and the porous carbon core; The nitrogen element is present in the porous carbon core in the form of pyridinic nitrogen, pyrrolic nitrogen and / or graphitic nitrogen; The phosphorus element is distributed in the porous carbon core at the molecular and / or atomic level; The organic cracked carbon coating layer is distributed in the pores and outer surface of the porous carbon core.
2. The silicon-carbon negative electrode material according to claim 1, characterized in that: The conductive carbon additive accounts for 0.01wt% to 1wt% in the silicon-carbon negative electrode material; The total proportion of the nitrogen element and the phosphorus element in the silicon-carbon negative electrode material is 0.01wt%~1wt%; The average particle size D50 of the silicon-carbon negative electrode material is 0.5 μm to 5 μm.
3. The silicon-carbon negative electrode material according to claim 1, characterized in that: The conductive carbon additive includes at least one of zero-dimensional conductive carbon, one-dimensional conductive carbon and two-dimensional conductive carbon; The size of the zero-dimensional conductive carbon is 0.1nm~100nm; The one-dimensional conductive carbon has a diameter of 0.1 nm to 50 nm and a length of 100 nm to 2000 nm; The two-dimensional conductive carbon has a thickness of 0.1 nm to 10 nm and a diameter of 100 nm to 500 nm.
4. The silicon-carbon negative electrode material according to any one of claims 1 to 3, characterized in that: The pore volume of the silicon-carbon negative electrode material is less than 0.01 cm³ / g; The most probable pore size of the silicon-carbon negative electrode material is below 3 nm; The specific surface area of the silicon-carbon negative electrode material does not exceed 5m² / g.
5. The silicon-carbon negative electrode material according to claim 1, characterized in that: The grain size of the nano-silicon is below 2 nm; The proportion of the nano-silicon in the silicon-carbon negative electrode material is 10wt% to 90wt%; The organic cracked carbon coating layer accounts for 0.1wt% to 10wt% in the silicon-carbon negative electrode material.
6. A method for preparing the silicon-carbon negative electrode material according to any one of claims 1 to 5, characterized in that: The following steps are involved: The hard carbon precursor is pyrolyzed and carbonized to obtain porous carbon, the porous carbon is used to adsorb silane compounds, and then the silane compounds are pyrolyzed in the porous carbon to deposit nano-silicon particles, and then the pores and outer surface of the porous carbon core are coated with an organic cracked carbon layer to obtain the silicon-carbon negative electrode material; The hard carbon precursor is doped with conductive carbon additives, nitrogen and phosphorus.
7. The preparation method according to claim 6, characterized in that: The method for preparing the hard carbon precursor comprises the following steps: The soluble biomass raw material is mixed with a conductive carbon additive, a nitrogen compound, a phosphorus compound and water to react, so that the biomass raw material is dehydrated and polymerized to obtain the hard carbon precursor; Wherein, the biomass raw material includes at least one of monosaccharides, disaccharides and polysaccharides; The temperature of the mixed reaction is 150°C to 375°C.
8. The preparation method according to claim 6, characterized in that: The temperature of the pyrolysis carbonization is 400° C. to 1000° C., and the time of the pyrolysis carbonization is 1 h to 12 h.
9. The preparation method according to claim 6, characterized in that: The silane compound is thermally decomposed at a temperature of 400° C. to 700° C., and the thermally decomposed time is 1 h to 12 h.
10. Use of the silicon-carbon negative electrode material according to any one of claims 1 to 5 in a lithium-ion secondary battery.
Citation Information
Patent Citations
High-rate spherical hard carbon composite material as well as preparation method and application thereof
CN114420939A
High-capacity hard carbon fast-charging negative electrode material as well as preparation method and application thereof
CN114695894A
Silicon-carbon composite silicon-based negative electrode material and preparation method thereof, negative electrode and lithium ion battery
CN116825994A
Silicon-carbon negative electrode material, preparation method and application
CN118156472A
